(untitled) (Janaki Medical College Journal of Medical Science, 2025)
Background & Objectives: Thyroid disorders are common in pregnancy and associated with a higher risk of maternal and fetal complications. Early detection and intervention can prevent most of those complications. This study, conducted in a teaching hospital in the Madhesh province of Nepal, aimed to assess the prevalence of thyroid disorders in the first trimester of pregnancy in this region. Material and Methods: A cross-sectional observational study was conducted at Janaki Medical College Teaching Hospital, Dhanusha, Nepal, over six months, from August 2021 to February 2022, after taking ethical clearance. All the females in their first trimester of pregnancy who gave their consent were included in this study. Blood samples were collected for thyroid function test in the early morning after overnight fasting. Results: Among 180 pregnant women, 80% were euthyroid and 20% had thyroid dysfunction. Subclinical hypothyroidism (12.22%) was most common, followed by overt hypothyroidism (6.11%) and subclinical hyperthyroidism (1.67%). No cases of overt hyperthyroidism were detected. Conclusion: Thyroid dysfunction, particularly subclinical hypothyroidism, was common among pregnant women studied. Routine screening may help to prevent adverse maternal and fetal outcomes.